Analysis of the law for the integration of non-conventional renewable energy sources (law 1715 of 2014) and its complementary decrees in Colombia (2019)
This paper presents a description of the regulations implemented in Colombia, from Law 1715 of 2014 until nowadays. The main decrees established for the development of projects with non-conventional sources of energy are described, as well as the steps to follow in order to obtain the tax benefits allowed by this law. The different scenarios for the development of photovoltaic projects are also identified, both by type and by size, describing the different procedures to be followed as well as the possible advantages and/or disadvantages of each one. © 2019 IEEE.